2020
DOI: 10.1093/rheumatology/kez642
|View full text |Cite
|
Sign up to set email alerts
|

Myofascia-dominant involvement on whole-body MRI as a risk factor for rapidly progressive interstitial lung disease in dermatomyositis

Abstract: Objective Rapidly progressive interstitial lung disease (RPILD) is a major cause of death in patients with DM. Although clinically amyopathic DM (CADM) represents risk for RPILD, the incidence rate of RPILD in patients with CADM varies widely. Whole-body (WB) MRI can reveal involvement of systemic muscle and myofascia. The objective of this study was to explore the risk factors for RPILD in patients with DM using WB-MRI. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In this study, all IIM-ILD patients received potent immunosuppressive therapy. However, the incidence of RP-ILD still amounted to 23.5% in the control group, which is similar to the incidence of rapid progression/acute exacerbation in previous reports of IIM-ILD (24-38%) and IPF (8.6-23.9%), but higher than the incidence in Ssc-ILD (9.4%) (10)(11)(12)(13). Efficacy and tolerability of nintedanib in IIM-ILD patients were hereby a worthy subject.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, all IIM-ILD patients received potent immunosuppressive therapy. However, the incidence of RP-ILD still amounted to 23.5% in the control group, which is similar to the incidence of rapid progression/acute exacerbation in previous reports of IIM-ILD (24-38%) and IPF (8.6-23.9%), but higher than the incidence in Ssc-ILD (9.4%) (10)(11)(12)(13). Efficacy and tolerability of nintedanib in IIM-ILD patients were hereby a worthy subject.…”
Section: Discussionsupporting
confidence: 84%
“…Idiopathicinflammatory-myopathy-related ILD (IIM-ILD) is frequently aggressive and refractory to conventional therapies including glucocorticoids and immunosuppressive drugs (7)(8)(9). In different studies, the incidences of rapidly progressive interstitial lung disease (RP-ILD) in IIM patients were relatively high (24-8%) compared to those in idiopathic pulmonary fibrosis (IPF, 8.6-23.9%) and systemic-sclerosis-related ILD (Ssc-ILD, 9.4%) (10)(11)(12)(13). RP-ILD has been taken as a major cause of mortality in IIM patients (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that among DM, including amyopathic patients, a predominant fascia involvement was an independent risk factor for rapidly progressive interstitial lung disease (54). Some authors (27) argued that WB MRI could assess the whole body musculature and detect neoplasia at the same time.…”
Section: Mri For Iim Prognosis and Extraskeletal Muscular Complicationsmentioning
confidence: 99%
“…It was shown that among DM, including amyopathic patients, a predominant fascia involvement was an independent risk factor for rapidly progressive interstitial lung disease (54).…”
Section: Muscle Mri For Iim Diagnosismentioning
confidence: 99%
“…7 Whole-body MRI (WB-MRI) was recently reported to be useful in revealing the disease-specific distribution of affected muscles and clinically asymptomatic muscle involvements in some subtypes of IIMs. 8 , 9 To clarify the involvement of the thoracoabdominal trunk muscles in IIMs, we evaluated systemic skeletal muscles, focusing not only on the limbs but also on the trunk, by applying WB-MRI STIR images in 10 Japanese patients with IIMs.…”
Section: Introductionmentioning
confidence: 99%